Prenatal stress induces vulnerability to nicotine addiction and alters D2 receptors' expression in the nucleus accumbens in adult rats. (24th September 2015) - Said, N.; Lakehayli, S.; El Khachibi, M.; El Ouahli, M.; Nadifi, S.; Hakkou, F.; Tazi, A.
Highlights: Nicotine induces CPP in rats at the dose of 0.5 mg/kg. Prenatal stress intensifies nicotine-induced CPP in adult rats. Prenatal Stress increases DRD2 expression levels in the nucleus accumbens. DRD2 expression is downregulated in the nicotine-treated prenatally stressed rats. Abstract: Prenatal stress (PS) can induce several long-lasting behavioral and molecular abnormalities in rats. It can also be considered as a risk factor for many psychiatric diseases like schizophrenia, depression or PTSD and predispose to addiction. In this study, we investigated the effect of prenatal stress on the reinforcing properties of nicotine in the CPP paradigm. Then, we examined the mRNA expression of the D2 dopaminergic receptors using the quantitative real-time PCR technique in the nucleus accumbens (NAcc). We found that prenatally stressed rats exhibited a greater place preference for the nicotine-paired compartment than the control rats. Moreover, we observed an overexpression of the DRD2 gene in adult offspring stressed in utero and a downregulation in the PS NIC group (PS rats treated with nicotine) compared with their control counterparts (C NIC). These data suggest that maternal stress can permanently alter the offspring's addictive behavior and D2 receptors' expression.